ECOLOGICAL PRESERVATION AS REPRESENTED IN RENA PRIEST’S POEMS - Winarti; Aris Hidayatulloh (International Journal of English Learning and Applied Linguistics (IJELAL), 2026)
This study examines ecological preservation in Rena Priest’s poems The Forest for the Trees, The Index, and Tour of a Salmonberry through an ecocritical perspective. Literature plays an important role in raising environmental awareness by representing ecological crises and human relationships with nature. Although ecocriticism has been widely discussed in literary studies, few studies specifically examine ecological preservation in Priest’s poetry through green literature discourse. The selected poems are significant because they represent contemporary environmental concerns, Indigenous ecological perspectives, and interconnected relationships between humans and nature. This study aims to analyze how ecological preservation is represented through imagery, symbolism, and narrative elements in the selected poems. The research employs a qualitative descriptive method using an ecocritical approach. Data were collected through documentation and close reading techniques and analyzed through thematic interpretation. The findings reveal three major ecological representations: wilderness destruction in The Forest for the Trees, environmental apocalypse in The Index, and ecological harmony and interdependence in Tour of a Salmonberry. The study demonstrates that Priest’s poetry promotes environmental awareness, ecological responsibility, and sustainable relationships between humans and nature while contributing to contemporary ecocritical studies through Indigenous ecological perspectives and poetic representation.